Hepatitis C Among High-Risk Alabamians: Disease Burden and Screening Effectiveness. (2nd September 2020) - Lee, Anthony B; Karumberia, Sandra; Gilmore, Ashley; Williams, Ebony; Bruner, Nichole; Overton, Edgar Turner; Saag, Michael S; Franco, Ricardo A
Abstract: Background: The effectiveness of hepatitis C testing and linkage-to-care (LTC) is poorly characterized in low-resource jurisdictions facing gaps in harm reduction, including illegality of syringe exchange services. Effectiveness of a community-based test/LTC program was evaluated in Alabama. Methods: In 2016–2018, shelters, drug treatment centers (DTCs), AIDS organizations, and Federally Qualified Health Centers (FQHCs) engaged in screening/LTC. A coordinator navigated individuals to confirm viremia and link to substance use treatment or primary care with hepatitis C prescribers. Results: Point-of-care (POC) tested 4293 individuals (10% [427] antibody-positive, 71% [299/419] RNA performed, 80% [241/299] viremia confirmed) and 93% linked to care (225/241). Electronic medical record (EMR)-based reflex strategy screened 4654 (15% [679] antibody positive, 99% [670/679] RNA performed, 64% [433/679] viremia confirmed) and 85% linked to care (368/433). We observed higher odds of RNA confirmation in EMR-based reflex versus POC (OR, 2.07; P  < .0001) and higher odds of LTC in EMR-based reflex versus POC (OR, 1.51; P  < .0001). Overall, 53% individuals tested were nonbaby boomers. Conclusions: In Alabama, screening at high-risk settings identified significant hepatitis C burden and reflex testing outperformed point-of-care linkage indicators. Colocating testing in DTCs and treatment in FQHCs provided key LTC venues to at-risk younger groups.